PENGARUH BIAYA OPERASIONAL-PENDAPATAN OPERASIONAL, PERTUMBUHAN ASET DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSET - Adnyana, Candra Sudha; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
Return On Asset is one of the ratios that are very important for any financial institution or company as it relates to sustainable and stability of any financial institution or company. In addition, to measure the company's ability to generate profits from investing activities. To generate high profit in each period, the company needs to consider all the factors that may affect the return on assets. The purpose of this study was to determine the effect of operational cost in operating income, the growth of assets and non-performing loans to partially return on assets. Research was conducted on Credit Institutions village in Buleleng. Data collected by means of documentation. Data analysis technique used is multiple linear regression. Based on the results of analysis show that the operating costs-operating income and non-performing loans significantly influence the return on assets. As for asset growth seignifikan no effect on return on assets.
Keywords: return on assets,operating cost-operating income, asset growth, non performing loan